DEVELOPMENT AND IMPLEMENTATION OF SMALL WIRELESS ECG DEVICES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the development and production of a small, expanded, affordable, and remote ECG device.